The Existence of Barzanji in The Modern Civilization as a Local Islamic Tradition in Bugis Land in the Frame of Postmodrnisme - Fatimah Fatimah; Winona Lutfiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
The tension between Islam and locality is an endless discussion. This cannot be separated from the classification of Islamologists. This classification creates a stereotype that Islam developing in Indonesia is considered an impure periphery of Islam. In addition, the threat to local Islamic traditions caused by the globalization development needs atten- tion because it threatens the existing diversity. This research is classified as qualitative.The data areobtained by the literature study method from written materials such as manuscripts, boohs, magazines, newspapers, and other documents. The data processing techniques arequoting, re- ducing data so that there is no overlapping data, classifying data, identi- fying data by re-cheching, and using the truly valid and relevant data. The results show that the existence of local Bugis culture, barzanji, still becomes a sacred ritual and a custom in the globalization development, so people who do not carry out the barzanji ritual in a traditional cer- emony are considered as violating customs. Barzanji persists in the glo- balization development because it is included in traditional rituals and has become a culture. Thus, the values of religious teachings will still exist if they are preached using cultural means. Besides, the existence of culture is also increasingly maintained because it is bound by religious values.